"Man kan inte bara gympa sig igenom ämnet": Hur fem idrottslärare på högstadiet legitimerar skriftliga praktiker i ämnet idrott och hälsa - Norberg, Anna-Maija (Educare, 2021)
This article investigates how five teachers in Physical Education and Health (PEH) draw on different discourses of legitimation and delegitimation of writing practices in PEH. The data consist of transcripts of audio recordings of interviews with the five teachers. Firstly, the recordings were analyzed using van Leeuwen’s (2007) legitimation framework. Secondly, the lexical choices were analyzed to identify different discourses of writing (Ivanič, 2004). Results show that a social practices discourse dominates in the data analyzed, most commonly realized through a rationalization type of legitimation. Students’ linguistic difficulties or unwillingness to write in PEH, i.e. writing with obstacles, is another discourse of writing found in the data. Overall, the teachers tend to legitimate writing practices but report on students’ delegitimation of the same practices, which teachers need to manage. The use of texts is legitimated as practical, timesaving and a recognized tool for instruction and assessment. Writing practices and the use of texts can contribute to the raise the status of PEH and reach long-term goals in PEH and for students’ learning at large. On the other hand, writing and text practices steal time from the core content in PEH and may not suit students who are successful in other parts of PEH.